On the identities of Callianassa bouvieri Nobili, 1904, C. maldivensis Borradaile, 1904, and C. gravieri Nobili, 1905 (Crustacea: Decapoda: Callianassidae): a morphometric approach - Dworschak, Peter C. (Zootaxa, 2012)
Recent samplings of callianassid shrimp from various habitats, together with the study of type specimens, show that Cal-lianassa gravieri Nobili, 1905 is a junior synonym of Callianassa bouvieri Nobili, 1904. Callianassa maldivensis Borra-daile, 1904, which had been synonymised with the latter, is a separate species. Morphometric analysis of more than 250specimens of these shrimps, which are assigned here to the genus Paratrypaea Komai & Tachikawa, 2008, show that P.bouvieri males and females have unequal chelipeds, whereas P. maldivensis has males with unequal chelipeds and femaleswith equal chelipeds. In addition, both species differ by the presence/absence and size of a median spine on the posteriortelson border. Male P. bouvieri and P. maldivensis are superficially similar but can be differentiated based on numerouscharacters of the major chelipeds, which are illustrated here in detail. The two species occur in different habitats, P. bou-vieri in the intertidal, often near mangroves, P. maldivensis usually sublittoraly near patchy corals. The importance of size and sex when comparing callianassid species is discussed.